ANALISIS TINGKAT KEPATUHAN PENGUNGKAPAN CSR PADA INDUSTRI SEMEN, SEKTOR PERTAMBANGAN DAN SEKTOR PERBANKAN PERIODE 2013-2014 - Magfiroh, Alisa Anggarani (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
This research aims to examine the industrial sectors performing the highest compliance level of CSR disclosure and their fluctuations in accordance with G4 Sustainability Reporting Guidelines standard core. To achieve the goal, the researcher analyzed and measured the compliance level of CSR disclosures as documented in the sustainability report of 10 companies in the area of cement industry, mining, and banking during 2013-2014 by following GRI guidelines. The research occupied descriptive-qualitative method and content-analysis technique. The result of the study showed that the highest compliance level of the CSR disclosure was achieved by cement industry, and subsequently followed by companies in mining sector and banking sector. The trend of the disclosure level elucidated slight increase and possibility of future’s high(er) level of CSR disclosures.Keywords : Corporate Social Responsibility (CSR), compliance, disclosure.